2015
DOI: 10.1007/s13197-015-1832-1
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting characteristics and associated changes in nutritional composition of cowpea (Vigna unguiculata)

Abstract: Cowpea (Vigna unguiculata), is an important arid legume with a good source of energy, protein, vitamins, minerals and dietary fibre. Sprouting of legumes enhances the bioavailability and digestibility of nutrients and therefore plays an important role in human nutrition. Improved varieties of grain cowpea viz. Pant Lobia-1 (PL-1) and Pant Lobia-2 (PL-2) and Pant Lobia-3 (PL-3) were examined for sprouting characteristics and associated changes in nutritional quality. Soaking time, sprouting time and sprouting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
93
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 23 publications
14
93
0
4
Order By: Relevance
“…The moisture content of black bean flours was within the range of 10.7-12.0% (Table I), with no significant differences among the samples, as previously reported for several common bean varieties (Khattab et al 2009;Du et al 2014). The 25.7% increase in crude protein observed for germinated black bean flour was higher than that reported for other legumes such as chickpea, cowpea, or mung bean (Uppal and Bains 2012;Devi et al 2015). As in previous reports, germination slightly increased the ash content, but these changes were not statistically significant (Devi et al 2015).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The moisture content of black bean flours was within the range of 10.7-12.0% (Table I), with no significant differences among the samples, as previously reported for several common bean varieties (Khattab et al 2009;Du et al 2014). The 25.7% increase in crude protein observed for germinated black bean flour was higher than that reported for other legumes such as chickpea, cowpea, or mung bean (Uppal and Bains 2012;Devi et al 2015). As in previous reports, germination slightly increased the ash content, but these changes were not statistically significant (Devi et al 2015).…”
Section: Resultssupporting
confidence: 73%
“…Proximate Composition. As in Devi et al (2015) and Uppal and Bains (2012), the crude fiber content increased in germinated samples, and dehulling only affected the content in raw seeds. Ash content of raw black bean flour ranged from 5.9 to 6.6%, with no significant differences among samples.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…According to Marton et al (2010), polysaccharides degrade into oligo and monosaccharides; fats into fatty acids and protein into free amino acids during germination. A study by Devi et al, (2015) showed a significant improvement in nutritional quality after sprouting of cowpeas at 25 °C for 24 h; protein increased by 9-12%, vitamin C increased by 4-38 times, phytic acid decreased by 4-16 times, trypsin inhibitor activity decreased by 28-55% and in-vitro protein digestibility increased by 8-20%. According to Jom et.…”
Section: Introductionmentioning
confidence: 99%
“…Dehulling reduces the dietary fiber and ash contents of pulses and increases protein, fat and starch contents as well as the availability of some nutrients. Soaking and germination also cause changes in nutritional composition and nutrient availability from grains (Devi et al 2015;Ghavidel and Prakash 2007;Kaur et al 2015;Lestienne et al 2005). Along with nutrients and bioactive components, pulses also contain anti-nutritional factors which may cause gastrointestinal discomforts or in extreme cases, even adverse reactions.…”
Section: Introductionmentioning
confidence: 99%